Impact of social comparison and peer pressure on iphone consumer happiness and innovativeness - Sari, Indah Permata; Atmaja, Ferry Tema (Manajemen dan Bisnis, 2024)
In the era of rapid technological advancement, the conventional use of smartphones has undergone a transformative paradigm shift. The presence of Apple's iPhone has become a significant entity surpassing mere communication functions. This research explores the dynamics linking social comparison, peer pressure, consumer innovativeness, and user satisfaction in the context of iPhone usage. Engaging 319 iPhone users in Indonesia through a comprehensive online survey, data was collected, and 150 respondents met the specified criteria. The study employs Partial Least Squares analysis using the SmartPLS4 software. Empirical findings reveal a positive correlation between social comparison and peer pressure, exerting a substantial influence on consumer innovativeness. Interestingly, social comparison also has a positive impact on consumer happiness. However, the research finds that while peer pressure significantly contributes to consumer innovativeness, it does not affect consumer happiness. This investigation underscores the crucial role of social comparison and peer pressure in shaping consumer innovativeness and happiness. The study elucidates the complex interaction between psychological and social factors. By understanding the desire to differentiate oneself and seek social acceptance, this research enhances our understanding of consumer decision-making in iPhone usage, facilitating diverse perspectives on technology as a crucial element in social identity construction.